Non-linear MHD simulations of ELMs in JET and quantitative comparisons to experiments. (13th November 2015) - Pamela, S; Eich, T; Frassinetti, L; Sieglin, B; Saarelma, S; Huijsmans, G; Hoelzl, M; Becoulet, M; Orain, F; Devaux, S; Chapman, I; Lupelli, I; et al.
Abstract: A subset of JET ITER-like wall (ILW) discharges, combining electron density and temperature as well as divertor heat flux measurements, has been collected for the validation of non-linear magnetohydrodynamic (MHD) simulations of edge-localised-modes (ELMs). This permits a quantitative comparison of simulation results against experiments, which is required for the validation of predicted ELM energy losses and divertor heat fluxes in future tokamaks like ITER. This paper presents the first results of such a quantitative comparison, and gives a perspective of what will be necessary to achieve full validation of non-linear codes like JOREK. In particular, the present study highlights the importance of pre-ELM equilibria and parallel energy transport models in MHD simulations, which form the underlying basis of ELM physics.